2004
DOI: 10.1124/jpet.104.066639
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Artichoke (Cynara scolymus L.) Up-Regulate Endothelial-Type Nitric-Oxide Synthase Gene Expression in Human Endothelial Cells

Abstract: Nitric oxide (NO) produced by endothelial nitric-oxide synthase (eNOS) represents an antithrombotic and anti-atherosclerotic principle in the vasculature. Hence, an enhanced expression of eNOS in response to pharmacological interventions could provide protection against cardiovascular diseases. In EA.hy 926 cells, a cell line derived from human umbilical vein endothelial cells (HUVECs), an artichoke leaf extract (ALE) increased the activity of the human eNOS promoter (determined by luciferase reporter gene ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 37 publications
7
65
1
4
Order By: Relevance
“…Enhancement of extraction from plant materials by the fluidized bed method indicate that the technique promotes the release of various phenolic compounds. The high flavonoid content of the fliuidized bed extracts is significant in view of the claimed vasculoprotector and antiatherosclerotic effects of these compounds [4]. Thus artichoke extracts may be of use in reducing blood lipids, and when taken together with its antioxidant property, the extract could be potentially useful for cardiovascular protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement of extraction from plant materials by the fluidized bed method indicate that the technique promotes the release of various phenolic compounds. The high flavonoid content of the fliuidized bed extracts is significant in view of the claimed vasculoprotector and antiatherosclerotic effects of these compounds [4]. Thus artichoke extracts may be of use in reducing blood lipids, and when taken together with its antioxidant property, the extract could be potentially useful for cardiovascular protection.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that artichoke is rich in fiber and low in fat. Thus, its health benefits were due to its high fiber content [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic contents in leaf and seed of Cynara cardunculus were similar and two times higher than those in flower heads [16]. The organic subfraction of artichoke is rich in polyphenolic compounds, with caffeoylquinic acids and flavonoids as the major chemical constituent [32]. In leaf extracts of commercially available artichoke (C. scolymus) a number of compounds were identified, including 8-deoxy-11-hydroxy-13-chlorogrosheimin, cryptochlorogenic acid, chlorogenic acid, neochlorogenic acid, cynarin, cynaratriol (tentatively), grosheimin, 8-deoxy-11,13-dihydroxygrosheimin, luteolin-7-O-rutinoside, luteolin-7-O-glucoside, and cynaropicrin [18].…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, our studies have demonstrated that ursolic acid (also present in Salviae miltiorrhizae radix) [24], betulinic acid (also a constituent of Zizyphi spinosae semen) [24], luteolin and cynaroside (also constituents of artichoke, Cynara scolymus L.) [25] are eNOSupregulating compounds. Ursolic acid and betulinic acid are two of the main PVL triterpenoids; luteolin and cynaroside are two of the main PVL flavonoids [23].…”
Section: Prunella Vulgaris L (Pvl)mentioning
confidence: 99%